2x-9y+9x+6y=

Simple and best practice solution for 2x-9y+9x+6y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-9y+9x+6y= equation:


Simplifying
2x + -9y + 9x + 6y = 0

Reorder the terms:
2x + 9x + -9y + 6y = 0

Combine like terms: 2x + 9x = 11x
11x + -9y + 6y = 0

Combine like terms: -9y + 6y = -3y
11x + -3y = 0

Solving
11x + -3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3y' to each side of the equation.
11x + -3y + 3y = 0 + 3y

Combine like terms: -3y + 3y = 0
11x + 0 = 0 + 3y
11x = 0 + 3y
Remove the zero:
11x = 3y

Divide each side by '11'.
x = 0.2727272727y

Simplifying
x = 0.2727272727y

See similar equations:

| X-(0.1x)=180 | | 8y/9^2 | | (x-2y)(x-2y)-64=0 | | 0.8(5x+8)=3.5-(x-3) | | 9x^2-5x+364=0 | | whatis-4.5=-1.2k | | x-2y^2-64=0 | | B+29=84 | | =27+2(3f-19) | | 9x^2+20x+364=0 | | 0.08(6+x)=0.12x+0.12 | | 2x+3+2x-4=78 | | 200-x/6=500-x/6 | | 2x+7.5=x | | (x^2-1)(x^2-9)=0 | | 3xy^2+yx=0 | | 7.50x-8=60.50 | | -15+z=-16 | | 6x-60=-2x+20 | | 2v-6+4v=0 | | 5n*5n+16=61 | | 7-5x=2x+3 | | x*4/5=7/20 | | x*5/4=7/20 | | 8p-8+2p=-18 | | -50x^2+x^4+49=0 | | -2=7-2m-7m | | 5x-22=3(x+2) | | 9+2z-3=6z+8-3z | | x*2/3=1/10 | | 7y-7-5y+2=0 | | 1/4=8^3x-7 |

Equations solver categories